Inorganic fertilizer use and its association with rice yield gaps in sub-Saharan Africa - Johnson, J.M.; Ibrahim, A.; Dossou-Yovo, Elliott Ronald; Senthilkumar, Kalimuthu; Tsujimoto, Y.; Asai, H.; Saito, Kazuki (Elsevier, 2023)
Where and which countries should receive higher priority for improving inorganic fertilizer use in rice fields in sub-Saharan Africa (SSA)? This study addressed this question by assessing the spatial variation in fertilizer use and its association with rice yield and yield gap in 24 SSA countries through a systematic literature review of peer-reviewed papers, theses, and grey literature published between 1995 and 2021. The results showed a large variation in N, P, and K fertilizer application rates and rice yield and an opportunity for narrowing the yield gap by increasing N and P rates, especially in irrigated rice systems. We identified clusters of sites/countries based on nutrient input and yield and suggested research and development strategies for improving yields and optimizing nutrient use efficiencies. Further research is essential to identify the factors causing low fertilizer use and the poor association between its use and yield in rainfed systems.